External Morphological Study of Tabanus autumnalis L. 1761,(Diptera: Tabanidae) in Iraq - S. Jasim, Hassan; J. Sabr, Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work included external morphological study of horse fly Tabanus autumnalis L. 1761, which belongs to family Tabanidae order: Diptera. The study involved the most important taxonomic external characters of the: head, thorax, abdomen and their appendages which are: antenna, maxillary palp, wings, legs, spotting in coloring pattern of abdomen.